Activities for engaging schools in health promotion. Issue 4 (2014) - ,; ,; ,; ,; ,; ,; ,; ,; ,; ,
Abstract : Purpose – The purpose of this paper is to describe activities used to initiate health promotion in the school setting.Design/methodology/approach – Description of successful pilot Health Promoting School (HPS) initiatives in Canada and Uganda and the validated measures central to each program. Evaluation methodologies: quantitative data from the tools used complimented by descriptive/qualitative methods.Findings – Previously validated tools/methodologies used include: The World Health Organization (WHO) growth charts for comparison of children's height, weight, head circumference, and BMI against multi‐ethnic standards; a 24‐h dietary recall instrument to assess dietary diversity as a proxy measure of nutritional adequacy; urine analysis to evaluate baseline renal function and the effect of supplemental hydration; "photo‐voice" to aid discussion of personal and community issues of concern; "role play" to promote dialogue and promote social competence; and fitness training. Each activity can combine the "curriculum content" and "healthy practices" components central to HPS concepts. All activities engaged more than 95 percent of pupils enrolled, generated positive responses, and had the potential to impact behaviors and promote health.Practical implications – All the activities are inexpensive and straightforward to initiate, offer schools interested in health‐promotion‐driven education a broad range of potential "entry points" that can be matched to the interests/challenges of individual communities, and use validated methodologies aiding objective evaluation.Originality/value – These activities foster a community empowerment ("bottom up") approach, but are also relevant for policy makers exploring HPS to address disease prevention through lifestyle change ("top down" approach). Engagement of communities and ultimately their "ownership" of the HPS initiative have been achieved with these entry point activities.